pH Dependence of Cyanogen Potentials of Local Wines (Buruku and Pito) Using Cyanomethemoglobin Complex - O.S., Osuegba; V. O., Adeleke-Ajagbe; B. O., Atolaiye (RA Journal of Applied Research, 2022)
The cyanogen potentials of local wines (burukutu, pito,) and the effect of pH (5.6-9.0) on the samples was determined using cyanomethemoglobin complex method. A total of 108 test samples were analyzed and the hydrogen cyanide content was found to vary considerably from 0.0313±0.0052 mg/L to 0.2444±0.0010 mg/L. pito was found to have the highest cyanogen potential with mean concentration of 0.2444±0.0010 mg/L at pH of 8.4 and burukutu found to have the lowest cyanogen potential with mean concentration of 0.0313±0.0052 mg/L at pH of 8.2. The highest mean concentration of cyanogen potential found in this study (0.2444±0.0010 mg/L) is lower than the recommended WHO and ISO standard (10mg/kg; 0.5-3.5 mg/kg body weight) and thus the samples may be consumed without the risk of cyanide poisoning.